2012
DOI: 10.3389/fpsyt.2012.00088
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Parameters of Stimulation, Clinical Trial Design Characteristics, and Motor Outcomes in Non-Invasive Brain Stimulation in Stroke

Abstract: Introduction/Objectives: Repetitive transcranial magnetic stimulation (rTMS) and transcranial direct current stimulation are two powerful non-invasive neuromodulatory therapies that have the potential to alter and evaluate the integrity of the corticospinal tract. Moreover, recent evidence has shown that brain stimulation might be beneficial in stroke recovery. Therefore, investigating and investing in innovative therapies that may improve neurorehabilitative stroke recovery are next steps in research and deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
119
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(127 citation statements)
references
References 129 publications
5
119
0
3
Order By: Relevance
“…Further, these meta-analytic findings were consistent with previous systematic reviews and meta-analyses that reported benefits of the NIBS techniques on stroke motor function assessed by various clinical assessments [25,26,28]. Thus, the present findings extended the positive effects of NIBS techniques on stroke motor recovery as indicated by quantifying a common outcome measure, paretic limb force production.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Further, these meta-analytic findings were consistent with previous systematic reviews and meta-analyses that reported benefits of the NIBS techniques on stroke motor function assessed by various clinical assessments [25,26,28]. Thus, the present findings extended the positive effects of NIBS techniques on stroke motor recovery as indicated by quantifying a common outcome measure, paretic limb force production.…”
Section: Discussionsupporting
confidence: 79%
“…Previous meta-analysis studies reported that balanced cortical activity between M1 of the hemispheres following tDCS or rTMS protocols may contribute to motor improvements in paretic limbs (e.g., various clinical assessments or activities of daily living) [25][26][27][28]. However, Chhatbar and Feng pointed out that these meta-analytic findings are still susceptible to inconsistency in outcome measures as well as selection criteria [29].…”
Section: Introductionmentioning
confidence: 82%
“…Adeyemo et al (2012) demonstrated a significant effect size (0.58) of non-invasive brain stimulation on motor function. Bastani and Jaberzadeh, 2012 showed that anodal tDCS had a small non-significant effect size of 0.39 on hand function in stroke, but a moderate significant effect size of 0.59 on motor evoked potential amplitude.…”
Section: Introductionmentioning
confidence: 95%
“…Recent meta-analyses have explored the effect of tDCS in addition to rehabilitation on UE activity in stroke (Bastani and Jaberzadeh, 2012;Adeyemo et al, 2012;Butler et al, 2013;Elsner et al, 2013). Adeyemo et al (2012) demonstrated a significant effect size (0.58) of non-invasive brain stimulation on motor function.…”
Section: Introductionmentioning
confidence: 99%
“…NIBS, which is repetitive TMS (rTMS) [96,98] and transcranial direct current stimulation (tDCS) [124], over the primary motor cortex can modulate the excitability of the motor cortex [125] and is often used as an effective tool for enhancing behavioral training after stroke with hemiplegia [125][126][127][128]. Furthermore, the NIBS to the cerebellum modulates cerebellar excitability [98,[129][130][131], motor function [132,133], and motor learning [32,[134][135][136][137][138] in healthy population.…”
Section: Noninvasive Brain Stimulation (Nibs)mentioning
confidence: 99%